Junius Brutus Booth : Theatrical Prometheus. - Archer, Stephen M. (Southern Illinois University Press, 2010)
In this, the first thoroughly researched scholarly biography of British actor Junius Brutus Booth, Stephen M. Archer reveals Booth to have been an artist of considerable range and a man of sensitivity and intellect. Archer provides a clear account of Booth's professional and personal life and places him in relationship to his contemporaries, particularly Edmund Kean and William Charles Macready. From 1817 to 1852 Junius Brutus Booth toured throughout North America, enjoying a reputation as the most distinguished Shakespearean tragedian on the American continent. Still, he ye.